Thermal analysis of a parabolic trough collectors system coupled to an organic rankine cycle and a two-tank thermal storage system: case study of Itajubá-MG Brazil (2022)
This study examined an Organic Rankine Cycle powered by a parabolic trough collector and a two-tank thermal storage system based on the development of a mathematical model, for the conditions of the city of Itajubá in Brazil. First, geometrical optics and heat transfer models of the collector–receiver set were used to determine the thermal equilibrium of the solar thermal collector system and parameters such as the efficiency of the solar field, heat and optical losses, and thermal energy of the outlet fluid. Next, the thermal equilibrium of the Organic Rankine Cycle was found in order to establish its operational parameters. Finally, the behavior of the thermal storage system was analyzed through its modeling. Once the characterization of the storage system was completed, the integrated operation of the proposed system was evaluated. Given Itajubá’s weather conditions, the results indicate that an electricity generation system can be implemented with the Solel UVAC Cermet selective coating for the absorber tube, water as the heat transfer fluid, and R-245fa as the working fluid. Based on the solar irradiation profile (1 March 2019), the parabolic trough collectors provided 63.3% of the energy required by the Organic Rankine Cycle to generate 7.4 kW, while the thermal storage system provided 36.4% of the energy demanded by the power generation block. Additionally, the results demonstrate the main conclusions that the turbine’s efficiency was influenced by parameters such as rotational speed, which is affected by the turbine inlet temperature, which, in turn, depends on the behavior of the solar irradiation profile onsite.